Data preparation - Pyle, Dorian (Henry Stewart Talks, 2008)
Why prepare data?, Six foundations for data preparation and modeling, Applicability of general data preparation techniques, What is data preparation?, Ideal data, Selecting data for modeling, Tools, Techniques, Introducing information transmission, Where to represent complexity?, Information transmission by mode, Signal and noise, Practical results
Archived at 2022/03/17